Analisis Sistem Pemasaran Kopi Pembinaan di Kabupaten Dair Provinsi Sumatera Utara - Rudsel Triana; Yusniar Lubis; Erwin Pane (Universitas Medan Area, 2018)
Dairi Regency producing a variety of agricultural commodities, both from the plantation sector as well as food crops and horticulture. The role of the agricultural sector is very important so that the economy of Dairi Regency is very dependent on the agribusiness sector. The research aims to determine the business channel and functions of each agency channel business administration in coffee marketing at Dairi Regency. To analyzing the spread of marketing costs, price spread and share margin on each channel in coffee trading system at Dairi Regency. Analyze the efficiency of coffee marketing on each channel at Dairi Regency, and analyze the differences in the farmers' acceptance of each channel in the coffee marketing at Dairi Regency. The results showed that the marketing system consists of a three channel. The channel I showed that farmers sell the coffee with half dry skin directly to exporters at a price of Rp. 6.000,-/kg, than exporters sell the dry coffee at a price of Rp . 14.000/kg. The channel II shows that the semi-dried coffee farmers sell to local traders at a price of Rp. 13.100/kg, the next half-dried coffee beans are sold to exporters at a price of Rp. 13.900/kg, by removing exporters / dry coffee sells at a price of Rp. 29.300/kg. The channel III shows that farmers sell the coffee beans half-dried to the district collector for Rp. 11,600/kg, then semi-dried coffee sold to local traders at a price of Rp. 12,300/kg, and half dried beans sold to exporters at a price of Rp. 13.100/kg. by exporters release / sell the dry coffee at a price of Rp. 29.300/kg. Keywords : agribusiness, commerce, coffee.